2009
DOI: 10.1038/nn.2476
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid beta from axons and dendrites reduces local spine number and plasticity

Abstract: Excessive synaptic loss is thought to be one of the earliest events in Alzheimer’s disease. Amyloid beta (Aβ), a peptide secreted in an activity-modulated manner by neurons, has been implicated in the pathogenesis of Alzheimer’s disease by removing dendritic spines, sites of excitatory synaptic transmission. However, issues regarding the subcellular source of Aβ, as well as the mechanisms of its production and actions that lead to synaptic loss, remain poorly understood. In rat organotypic slices, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
266
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(300 citation statements)
references
References 50 publications
28
266
1
Order By: Relevance
“…A major secretion site of Ab seems to be distal axons/synapses (Lazarov et al 2002;Sheng et al 2002), but recently it was reported that Ab can be secreted from axons and dendrites and can elicit local effects on neighboring neurons ( Fig. 7C; Wei et al 2010). A detailed analysis aimed at determining the ratio of axonally versus dendritically secreted Ab, using for example cultured neurons in compartmentalized chambers, has not been performed.…”
Section: Subcellular Sites Of G-secretase-mediated App Processingmentioning
confidence: 99%
“…A major secretion site of Ab seems to be distal axons/synapses (Lazarov et al 2002;Sheng et al 2002), but recently it was reported that Ab can be secreted from axons and dendrites and can elicit local effects on neighboring neurons ( Fig. 7C; Wei et al 2010). A detailed analysis aimed at determining the ratio of axonally versus dendritically secreted Ab, using for example cultured neurons in compartmentalized chambers, has not been performed.…”
Section: Subcellular Sites Of G-secretase-mediated App Processingmentioning
confidence: 99%
“…Synapse loss is the most robust correlate of AD-associated cognitive deficits. In both AD patients and animal models of this disease, the greastest synapse loss is near senile plaques, indicating a link between Aβ pathology and synaptotoxicity in vivo [7,8] . Furthermore, AβOs have been www.chinaphar.com Zhang LL et al Acta Pharmacologica Sinica npg shown to downregulate the levels of two synaptic proteins, postsynaptic density-95 (PSD-95) and synaptophysin [9] .…”
Section: Introductionmentioning
confidence: 99%
“…The increase in release probability was associated with reduced paired-pulse facilitation such that excitatory synapses behaved like low-pass filters, facilitating low frequency activation of AMPA receptors in hippocampal slices. How this presynaptic facilitatory action relates to the putative negative feedback postsynaptic actions of endogenously-generated human Aß (Hsieh et al , 2006, Wei et al , 2010 is not clear. If confirmed, caution will be needed in the use of anti-Aß therapies that might interfere with such physiological processes.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Li et al (2009) reported that cell-derived oligomeric human Aß acutely increased extracellular glutamate concentrataion in hippocampal slices. Whereas low nanomolar concentrations of these oligomers reduced the amplitude of AMPA receptor-mediated (Cerpa et al , 2010, Kessels et al , 2010, Ronicke et al , 2010). …”
Section: Ampa ( -Aminomentioning
confidence: 99%
See 1 more Smart Citation